2019
DOI: 10.1074/mcp.ra119.001515
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy and Complementarity between ERAP1 and ERAP2 Revealed by their Effects on the Behcet's Disease-associated HLA-B*51 Peptidome*[S]

Abstract: HLA-B*51 is the main risk factor for Behç et's disease. ERAP1 and ERAP2 trim peptides in the endoplasmic reticulum to be presented by MHC-I molecules. ERAP1, but not ERAP2, is also associated with this disorder in epistasis with B*51. Inhibition of each or both enzymes allowed the identification of the specific role of these proteins and their cooperation on shaping the HLA-B*51 peptidome and provide a basis for their differential association with Behç et's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 90 publications
1
13
0
5
Order By: Relevance
“…In HLA-B*51:01, which virtually does not bind peptides with basic P1 residues, the main effect of ERAP2 expression, when ERAP1 was also present, was not on P1 residue usage but instead on an increased abundance of 8-mers, relative to 9-mers and longer peptides. This study (20) also showed that, in the absence of ERAP1, ERAP2 is able to process HLA-B*51 ligands in the ER, revealing a degree of functional redundancy, which is only evident upon absence of ERAP1. These previous studies show that the effect of ERAP2 on MHC-I peptidomes, although significant in all cases, is strongly dependent on the peptide specificity of each particular MHC-I molecule.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…In HLA-B*51:01, which virtually does not bind peptides with basic P1 residues, the main effect of ERAP2 expression, when ERAP1 was also present, was not on P1 residue usage but instead on an increased abundance of 8-mers, relative to 9-mers and longer peptides. This study (20) also showed that, in the absence of ERAP1, ERAP2 is able to process HLA-B*51 ligands in the ER, revealing a degree of functional redundancy, which is only evident upon absence of ERAP1. These previous studies show that the effect of ERAP2 on MHC-I peptidomes, although significant in all cases, is strongly dependent on the peptide specificity of each particular MHC-I molecule.…”
supporting
confidence: 52%
“…The influence of ERAP2 on MHC-I-bound peptidomes has been examined so far in HLA-B*27:05 (17,18), A*29:02 (19), and HLA-B*51:01 (20). The B*27:05 peptidome shows a relatively high frequency of peptides with basic P1 residues, and the overwhelming majority of HLA-B*27 ligands have R at P2.…”
mentioning
confidence: 99%
“…and Int_Rv (ACTTGTTACGTGCCTAGACCT). Transfected cells were cloned and the ERAP2 expression was analyzed by PCR and Western Blot as previously described (31). Two unedited (UN17, and UN20 with the complete ERAP2 sequence) and two homozygously edited (KO9, and KO19 without the ERAP2 exons 5 and 6) cell clones were selected.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The most frequent alleles resulted A*02 (38 pts) and A*01 (25 pts) for the locus A; B*18 (20 pts) and B*35 (20 pts) for the locus B; C*07 (43 pts) and C*04 (27 pts) for the locus C and DRB1*11(36 pts) and DRB1*03 (20 pts) for DRB1. In our analysis, we also included allele HLA-B*51 (17 pts) for its known correlation with common autoimmune diseases 15. Allele homozygosis for the loci A, B, C and DRB1 was detected in 10, 4, 11 and 13 patients, respectively.…”
mentioning
confidence: 99%